Effect of heavy metal speciation on nitrification inhibition - Semerci, Neslihan Yazıcı. (Thesis (Ph.D.)-Bogazici University. Institute of Environmental Sciences, 2007., 2007)
Industrial effluents and high-strength wastewaters such as landfill leachates may contain significant amounts of heavy metals. The presence of heavy metals causes toxicity in biological treatment systems. The toxic and inhibitory characteristics of heavy metals depend on several factors such as exposure time, type of buffer, pH, type and concentration of ligands and acclimation. Therefore, a quite high variation is seen in the reported inhibitory range for metals. Surprisingly, very little information exists on the importance of heavy metal speciation in nitrification inhibition studies. Furthermore, the behaviour of heavy metals under prolonged exposure times, acclimation, adaptation, shifts and changes in bacterial community have not been examined yet. The aim of this study was to investigate the influence of Cd and Zn speciation on nitrification inhibition in batch systems enriched in terms of nitrifiers and to investigate the response of nitrifying biomass to prolonged Cd exposure in a continuous-flow system. These experiments showed that the measurement methodologies applied in assessing heavy metal inhibition should be carefully selected since physical and chemical speciation highly affects inhibition. The activity of nitrifying bacteria in continuous-flow systems could change as a result of shifts in microbial community. It also showed the necessity of incorporation of molecular tools into heavy metal inhibition studies.|Keywords: Nitrification, heavy metals, inhibition, biosorption, activated sludge
Keywords: Nitrification.; Heavy metals.; Sewage -- Purification -- Activated sludge process.; Sewage -- Purification -- Heavy metals removal.